Progress and prospect of blue food research: Analysis based on “Web of Science” literature - ZHANG Yu, LIU Jiaming, ZHU He, ZHANG Jinhe, TIAN Qing, WANG Mengfan (Ziyuan Kexue)
[Objective] Blue food has become an important solution for human nutrition, health, and food security under the global sustainable development goals. Because of its nutritional health and environmental potential, it is becoming the focus of the transformation and upgrading of the food system. By comprehensively sorting out the development context and research trends of blue food, its hot topics and future development direction can be further summarized. [Methods] Based on the “Web of Science Core Collection (1985-2023)” as the data source, this study analyzed the relevant research results of blue food based on CiteSpace software, and discussed the research framework and future key issues of blue food from the perspective of geography. [Results] The findings are as follows: (1) Existing research has experienced three stages of steady growth at the initial stage, slow growth in the middle stage and rapid development in the recent period.The research fields are broad and there are numerous research institutions, but there exist issues such as insufficient theoretical construction and weak international exchanges and cooperation. (2) Existing studies continue to pay attention to aquaculture, food safety testing, consumer consumption, etc. In recent years, hot topics have paid more attention to human-land relationship and the construction of sustainable food systems, focusing on the nutrition and health value, resource and environmental effects, social and economic value, demand and consumption, and dietary recommendations of blue food. [Conclusion] By analyzing the progress of blue food research and constructing a framework for blue food studies from a geographical perspective, this paper suggests that future efforts should focus on the study of blue food consumption in different scenarios and groups, spatial and temporal differentiation of blue food production and consumption, multi-scale assessment and mechanism analysis of the environmental effects of blue food, the stability of blue food system and the response to future changes, and the multi-objective optimization of blue food consumption structure, so as to promote the theoretical improvement and practical innovation of blue food research in China.